2014
DOI: 10.1155/2014/217596
|View full text |Cite
|
Sign up to set email alerts
|

Fused Imidazopyrazoles: Synthetic Strategies and Medicinal Applications

Abstract: The current review summarizes the known synthetic routes of fused imidazopyrazoles. This review is classified into two main categories based on the type of annulations, for example, annulation of the imidazole ring onto a pyrazole scaffold or annulation of the pyrazole ring onto an imidazole scaffold. Some medicinal applications of imidazopyrazoles are mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Pure products 7 were isolated by silica gel column chromatography (EtOAc:hexane1:4 as eluent). (29), 243 (20), 189 (M + -CHCl 2 , 100), 171 (21), 157 (8), 145 (44), 128 (16), 104 (17), 77 (24), 51 (12)…”
Section: General Procedures For the Synthesis Of 3-aryl-5-dichloromet...mentioning
confidence: 99%
See 2 more Smart Citations
“…Pure products 7 were isolated by silica gel column chromatography (EtOAc:hexane1:4 as eluent). (29), 243 (20), 189 (M + -CHCl 2 , 100), 171 (21), 157 (8), 145 (44), 128 (16), 104 (17), 77 (24), 51 (12)…”
Section: General Procedures For the Synthesis Of 3-aryl-5-dichloromet...mentioning
confidence: 99%
“…The pyrazole core is a highly important scaffold in medicinal chemistry whose fusion with other pharmacophoric heterocyclic systems has revealed to be of great interest in the search for outstanding biological activities. Numerous comprehensive reviews have been recently devoted to this subject, for example, pyrazolopyrimidines [1][2][3], pyrazolopyrazines [4], pyrazoloquinazolines [5], pyrazolothiazoles [6], among others [7][8][9][10][11][12]. On the other hand, abundant studies on biological properties of oxazine derivatives have demonstrated that they are promising agents to develop drugs with sedative, analgesic, anticonvulsant, antipyretic, antimicrobial, antitubercular, antimalarial, antioxidant, and anticancer activities [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Imidazopyrazoles have been recognized as substances of significant chemical, biological and medicinal interest. 3,4 By far, the most well-known compounds are those pertaining to the imidazo [1,2-b]pyrazole family, which have been described as possessing noteworthy anticancer, [4][5][6] antibacterial, 7,8 and anti-inflammatory 9,10 properties, among others. 5-Aminopyrazoles, the synthetic methods for which have been extensively reviewed, 11 are the main preparative intermediates for imidazo[1,2-b]pyrazoles.…”
mentioning
confidence: 99%
“…32,33,36,40,41 However, synthetic methodology for obtaining imidazo [1,5-b]pyrazole derivatives is notably lacking, and very little is known about these compounds. 3,4 Only a few individual examples having this uncommon ring fusion have been previously prepared; for example, by cyclodehydration of substituted pyrazolylmethylacetamides leading to 2,3-dihydroimidazo [1,5-b] derivatives related to cyclized histamine, 43 preparation of 2,3-dihydro-1H-imidazo [1,5-b]pyrazole-4,6(3aH,5H)-dione from 1-(benzylideneamino)-5-(2-hydroxyethyl)hydantoin, 44 and the synthesis of hexahydro-4,4-dimethyl-1,3a-diaryl-6-oxo-1H-imidazo [1,5-b]pyrazole-3-carbonitriles from -aminoisobutyrophenone phenyl hydrazones. 45 Concerning imidazopyrazolones, studies on the synthesis, properties and usefulness of substances exhibiting [1,2-b], [46][47][48][49][50] [4,5-c], 51,52 and [3,4-b] 45 ring systems have been successful.…”
mentioning
confidence: 99%